Droplet growth in a bin warm-rain scheme with Twomey CCN activation - Grabowski, W; Andrejczuk, M; Wang, L (2011)
This paper discusses improvements to the bin warm-rain microphysics scheme that applies the Twomey approach to represent CCN activation. The Twomey approach relates the concentration of activated droplets to the maximum supersaturation experienced by the air parcel during activation and thus avoids complications of CCN size distribution and chemical composition that are considered in more complicated activation schemes. When using the traditional Twomey scheme, activated droplets are typically inserted into the first bin of the bin microphysics scheme. As shown in our previous study, this does not allow numerical convergence when the number of bins is increased. In addition, CCN characteristics are important for early growth of cloud droplets and it is unclear if an approach where such characteristics are not considered provides a valid strategy for modeling diffusional growth of small cloud droplets. We included relatively simple modifications to the bin warm-rain microphysics with Twomey approach to CCN activation and apply the improved scheme to idealized Lagrangian parcel simulations as well as 1D Eulerian updraft simulations. We compare results of the improved scheme with the benchmark results from a sophisticated aerosol activation and growth model. Two observationally-based aerosol characteristics are employed in the comparison, the pristine from DYCOMS and polluted from VOCALS. The results suggest that the improved bin scheme compares relatively well with the benchmark, and leads to numerical results that are significantly less sensitive to the number of bins applied. The results also suggest the minimum bin and spatial resolutions that need to be used in the large-eddy simulation to investigate with confidence the impact of cloud turbulence on warm-rain development. © 2010 Elsevier B.V.